Analisis Structural Equation Modeling Partial Least Square Terhadap Faktor Yang Mempengaruhi Keputusan Pembelian Konsumen Pada Produk AMDK - Cindy Caroline; Ira Setyawati; Epha Diana Supandi (Performa: Media Ilmiah Teknik Industri, 2024)
Increasingly fierce competition requires companies to produce a good brand image. This encourages entrepreneurs to be more effective, efficient, creative, innovative and adaptive, so that companies are able to choose the right strategy. Companies need to know the position of their product brands in the minds of consumers and then develop strategies to further increase consumer loyalty. This study was conducted to analyze the factors of quality, price, and brand image on purchasing decisions. Data analysis was carried out by Partial Least Square - Structural Equation Model using SmartPLS statistical software. With the results of the R2 output of 64% and the significance test with the bootstrapping process, the price, quality and brand image factors have a significant influence on purchasing decisions. The variable that has the most influence on purchasing decisions is brand image with an original sample value of 0.426.